2013
DOI: 10.3892/ijmm.2013.1480
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a transgenic mouse model of corneal dystrophy overexpressing human BIGH3

Abstract: Abstract. This study aimed to establish a transgenic mouse model of corneal dystrophy (CD) overexpressing the human transforming growth factor, β-induced, 68 kDa (TGFBI, also known as BIGH3) gene. A purified and linearized recombinant plasmid carrying the expression cassette BIGH3-IRES-EGFP was microinjected into the pronuclei of C57BL/6J mouse fertilized eggs under the control of the phosphoglycerate kinase (PGK) promoter. The expression of human BIGH3 in the transgenic mice was confirmed by PCR using DNA ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Thus, the study concludes that TGFBIp might be involved in anterior segment morphogenesis and eye development (Kim et al, 2007). Another mouse model overexpressing human TGFBIp under the control of the phosphoglycerate kinase promoter showed similar corneal opacities when eyelids opened at approximately two weeks after birth (Liao et al, 2013). This study did not perform any histological examination of the anterior segment of the transgenic mice, and we cannot conclude if the opacities are caused by TGFBIp accumulation or disrupted corneal endothelium.…”
Section: Overexpression Mouse Modelsmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, the study concludes that TGFBIp might be involved in anterior segment morphogenesis and eye development (Kim et al, 2007). Another mouse model overexpressing human TGFBIp under the control of the phosphoglycerate kinase promoter showed similar corneal opacities when eyelids opened at approximately two weeks after birth (Liao et al, 2013). This study did not perform any histological examination of the anterior segment of the transgenic mice, and we cannot conclude if the opacities are caused by TGFBIp accumulation or disrupted corneal endothelium.…”
Section: Overexpression Mouse Modelsmentioning
confidence: 82%
“…Protein domain 1 Phenotype 2 Age of onset (decade) Reference V113I FAS1-1 GCD1 Third (Zenteno et al, 2006) V113I/L558P FAS1-1/FAS1-4 Variant LCD Fourth -Fifth (Ann et al, 2017) D123H FAS1-1 Atypical GCD Fifth (Ha et al, 2003) R124C FAS1-1 LCD1 First -Second (Munier et al, 1997) R124C/G470Ter FAS1-1/FAS1-3 LCD1 Eighth (Sakimoto et al, 2003) R124C/A546D FAS1-1/FAS1-4 Variant LCD Second -Third (Cao et al, 2017) R124H FAS1-1 GCD2 First -Fourth (Munier et al, 1997) R124H/P130Ter FAS1-1 GCD2 Third (Yam et al, 2012) R124H/R179Ter FAS1-1 GCD2 Fourth (Song et al, 2015) R124H/N544S FAS1-1/FAS1-4 GCD2-LCD Seventh (Yamada et al, 2009) R124L FAS1-1 RBCD First -Second (Okada et al, 1998) R124L/T125- (Han et al, 2014) Overexpression (liver) Anterior segment dysgenesis (Kim et al, 2007) Overexpression Corneal opacities (Liao et al, 2013) R555W mutant (overexpressed) Retinal degeneration (Bustamante et al, 2008) R124H mutant Corneal opacities (Yamazoe et al, 2015)…”
Section: Mutationsmentioning
confidence: 99%
“…However, mutated TGFBI was expressed in the retina and induced an age‐dependent retinal degeneration both functionally (ERG) and histologically, suggesting that altered TGFBI may affect photoreceptor survival. Using an identical promoter but a different transgenesis protocol, Liao, Cui, and Wang () established a transgenic mouse model overexpressing TGFBI. These mice displayed central corneal opacities in five out of seven transgenic mice…”
Section: Tgfbi Expression Role and Pathology In The Eye Of Humans Amentioning
confidence: 99%
“…photoreceptor survival. Using an identical promoter but a different transgenesis protocol,Liao, Cui, and Wang (2013) established a transgenic mouse model overexpressing TGFBI. These mice displayed central corneal opacities in five out of seven transgenic miceYamazoe et al (2015) reported a transgenic mouse model of GCD2 caused by the p.Arg124His variant, showing granular with or without lattice deposits in the center of the cornea.…”
mentioning
confidence: 99%
“…58 Overexpression of an Arg155Trp TGFbI variant transgenic mouse resulted in retinal photoreceptor atrophy, 59 but the same insertional promotor and another transgenesis protocol resulted in mice with central corneal opacities that were not microscopically phenotyped. 60 Deletion of TGFbI did not result in any ocular lesions, and the reported increased incidence of spontaneous tumors and 7,12-dimethylbenz[a]anthracene-induced skin tumors in these TGFbI À/À mice 67 is small.…”
Section: Comparative Literature Review Of Corneal Dystrophy In Animalmentioning
confidence: 81%